Perspectives on scaling production of adipose tissue for food applications. (January 2022) - Yuen Jr, John S.K.; Stout, Andrew J.; Kawecki, N. Stephanie; Letcher, Sophia M.; Theodossiou, Sophia K.; Cohen, Julian M.; Barrick, Brigid M.; Saad, Michael K.; Rubio, Natalie R.; Pietropinto, Jaymie A.; DiCindio, Hailey; Zhang, Sabrina W.; et al.
Abstract: With rising global demand for food proteins and significant environmental impact associated with conventional animal agriculture, it is important to develop sustainable alternatives to supplement existing meat production. Since fat is an important contributor to meat flavor, recapitulating this component in meat alternatives such as plant based and cell cultured meats is important. Here, we discuss the topic of cell cultured or tissue engineered fat, growing adipocytes in vitro that could imbue meat alternatives with the complex flavor and aromas of animal meat. We outline potential paths for the large scale production of in vitro cultured fat, including adipogenic precursors during cell proliferation, methods to adipogenically differentiate cells at scale, as well as strategies for converting differentiated adipocytes into 3D cultured fat tissues. We showcase the maturation of knowledge and technology behind cell sourcing and scaled proliferation, while also highlighting that adipogenic differentiation and 3D adipose tissue formation at scale need further research. We also provide some potential solutions for achieving adipose cell differentiation and tissue formation at scale based on contemporary research and the state of the field.